A case of ventricular ectopy eliminated by catheter ablation: Diversity of the potentials on the left coronary cusp. Issue 5 (4th July 2018) - Kajiyama, Takatsugu; Hachiya, Hitoshi; Iesaka, Yoshito
Abstract: An 18‐year‐old man without organic heart disease underwent catheter ablation for frequent monomorphic ventricular ectopic beats(VEBs). The origin of the VEB was presumed located on the left coronary cusp(LCC) regarding his electrocardiography. Local activation in the right ventricular outflow tract was not so early. On the LCC, four different prepotentials were obtained by slight relocation of the catheter. Finally, on the site with positive discrete prepotential recorded on the distal electrodes, an application of radiofrequency current immediately eliminated the VEB. Although LCC is considered as a small structure, detailed mapping may be important to find the most optimal ablation site.